Quantitative Assessment of Work-related Hand-arm Vibration Exposure Among Workers in the Construction, Underground Coal Mining, Wood Working, and Metal Working Industry: The German Hand-arm Vibration Study - Yi Sun; Frank Bochmann; Winfried Eckert; Benjamin Ernst; Christian Freitag; Uwe Kaulbars; Uwe Nigmann; Christina Samel; Christian van den Berg; Nastaran Raffler (Safety and Health at Work)
Background: Standardized exposure assessments were conducted to quantify the historical occupational exposure to hand-arm vibration of workers in the German construction, underground coal mining, woodworking, and metalworking industries. Methods: A two-step approach was used to assess historical vibration exposure. In the first step, individual work histories were reconstructed by standardized personal interviews. The interview focused on the identification of relevant power tools used throughout the working life. In the second step, an equipment-exposure-matrix was constructed by industrial hygiene measurements. By linking the power tools in the work history to the equipment-exposure-matrix, individual daily, and long-term vibration exposures can be quantified. Results and conclusions: A total of 423 power tools were identified for 5,115 exposure segments over a period of 50 years. 97.2% of the vibration values were based on industrial hygiene measurements. The total vibration value (ahv) of the power tools used varied between 0.8 m/s2 and 65.2 m/s2 with a median value of 14.2 m/s2. The median value of cumulative vibration exposure is Dhv = 121,971 (range: 23-3,374,640) m2/s4·day, corresponding to a daily vibration exposure of ahv(8) = 7 m/s2 for 2489 working days (11.3 years).This study provides a detailed description of hand-arm vibration exposure among workers in the related industries studied. Our analyses indicate that the quantification of daily vibration exposure is often uncertain and should be interpreted with caution. In contrast, cumulative vibration exposure is a more reliable exposure parameter for describing general working conditions and for guiding the prevention and compensation of vibration-related health problems.